14 Car. 2, c.3 (1662) - (:unkn) unknown (My University, 1662)
Ordered deputy lieutenants to seize arms from any person "judge[d] dangerous to the Peace of the Kingdom."
Keywords: POSSESSION - DANGEROUS PERSONS